Building Sustainability Business Industry Palm Oil 4.0 Through A Green Human Resources Management, Green Innovation and Approach Green Commitment - Henny Hendarjanti (Universitas Trisakti, 2022)
Indonesia is the leading producer and exporter of palm oil worldwide and the world's top supplier of palm oil-based biofuel. Oil palm plantations in the Industrial Era 4.0 are required to increase production and productivity in an environmentally friendly and sustainable manner in the face of global competition. Various environmental issues have become a concern on world economic growth. There is a close relationship between the environment with production and the economy. The issue of global warming has become a central issue that poses a threat to the country's economic activities, production, and economic growth. The application of “Good Agricultural Practices” in the palm oil industry is accompanied by environmental policies, both mandatory and voluntary, as an effort towards business sustainability. One of which involves managing human resources in the business process of oil palm plantations to reduce greenhouse gas emissions. Implementation of the company's environmental policy to preserve nature through employee involvement in innovation and commitment to the environment. This writing aims to understand the framework that explains the relationship between the variables of Green Human Resources Management (GHRM), Green Innovation, Green Commitment and Sustainability Business. This paper presents the theory of Green HRM, especially the behavior of Green Commitment and Green Innovation in an organization. This paper is obtained through library research by analyzing the relationship between variables. Focuses on the relationship between the variables of Green HRM, Green Innovation, Green Commitment and Sustainability Business which is expected to complement literacy of similar research in the future.